Bultmann se ontmitologiseringsprogram herwaardeer - Malan, Gert (Hervormde teologiese studies, 2000)
Bultmann's demythologising program reevaluated. The kerygma of the New Testament is depicted in the mythological language of a bygone mythological world-view. Bultmann suggested that demythologisation is necessary in order to explore the true Existenzverstandniss contained in the mythological concepts. Reaction to his program of demythologising was mostly negative, especially in South Africa. This article focuses on the necessity for demythologisation as well as Bultmann's definition of myth, in order to re-evaluate his program of demythologisation. Bultmann's demythologising program is considered as a responsible method for interpreting the texts of the New Testament.